Inhibition of Proinflammatory Cytokines and Mediators by Euphol - Pandey Anjali and Bani Sarang (Journal of Applied Pharmaceutical Science, 2013)
The anti-inflammatory properties of Euphol (EU) a diterpene, isolated from the rhizomes of the plant Euphorbia acaulis, were evaluated. This study was designed to examine the effects of EU on inflammation in a rat model of pleurisy compared with a steroidal anti-inflammatory drug (DEX, dexamethasone). The rat model of pleurisy was used to evaluate the effectiveness of EU on leukocyte migration, exudation volume, proinflammatory cytokines i.e. Tumor Necrosis factor α (TNFα), Interleukin-1 (IL-1β) and Interleukin-6 (IL-6) as well as on proinflammatory mediators PGE2, nitrite/nitrate levels, and LTB4. Pleurisy was induced by carrageenan (cg), administered by intra pleural route (i.pl.) and the leukocyte infiltration and inflammatory parameters analyzed 4 h after pleurisy induction. EU (8mg/kg-1, p.o.) treated groups caused significant decrease in the infiltration of neutrophils and exudate volume . There was an observed marked reduction in TNFα, IL-1β and IL-6 levels. Flow cytometric analysis of intracellular TNFα by leukocytes present in pleural exudates showed a significant decrease relative to the total extracellular TNFα inhibition in the pleural fluid. The proinflammatory mediators PGE2, LTB4 release and the nitrite/nitrate levels were remarkably deregulated which are interrelated to TNFα and IL-1β levels.
Keywords: Euphol (EU), Rat pleurisy, Leukocytes, Proinflammato